1988
DOI: 10.1182/blood.v71.1.86.bloodjournal71186
|View full text |Cite
|
Sign up to set email alerts
|

Vitronectin (S protein) augments the functional activity of monocyte receptors for IgG and complement C3b

Abstract: An arginine-glycine-aspartic acid sequence (RGD in the single letter code for amino acids) is present in the cell attachment site of both vitronectin and fibronectin. Inasmuch as fibronectin and synthetic peptides containing RGD enhance ingestion of opsonized particles by monocytes, we investigated the effects of vitronectin on phagocytosis by monocytes of sheep erythrocytes bearing IgG (EA) or complement C3b (EC3b). Peripheral blood monocytes were isolated by countercurrent elutriation and allowed to adhere t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…They were also localized continuously around inflammatory cells such as macrophages, neutrophils and lymphocytes that infiltrated into these regions, around sinusoidal endothelial cells, Ito cells and hepatocytes and in intercellular spaces among these cells. Parker, Frame and Elstad (38) reported that VN modulates interactions between inflammatory cells and opsonized particles. The results of our study support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…They were also localized continuously around inflammatory cells such as macrophages, neutrophils and lymphocytes that infiltrated into these regions, around sinusoidal endothelial cells, Ito cells and hepatocytes and in intercellular spaces among these cells. Parker, Frame and Elstad (38) reported that VN modulates interactions between inflammatory cells and opsonized particles. The results of our study support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins were transferred to nitrocellulose paper (Towbin et al, 1979). and the paper was incubated with TBS-milk at RT (Parker et al 1988). After 30 min the paper was washed with TBS.…”
Section: Methodsmentioning
confidence: 99%
“…Recently. vitronectin was shown to augment the activity of monocyte receptors for IgG and complement C3b (Parker et al 1988). and increased expression of vitronectin receptors appears to correlate with differentiation of monocytes into macrophages (Charo et al,198 7).…”
mentioning
confidence: 99%
“…Both fibronectin and S-protein belong to a family of adhesive proteins which share an Arg-Gly-Asp amino acid sequence in the cell attachment site [37]. The platelet receptor gpIIb-IIIa for Arg-Gly-Asp [36] is also present on monocytes [5,8] and may be the S-protein receptor on these cells [32]. The phagocytes may thus produce their own adhesion molecules, which bind to cellular receptors and take part in the attachmetit and also enhance the Fc and C3b receptor activities [32] of the cells in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet receptor gpIIb-IIIa for Arg-Gly-Asp [36] is also present on monocytes [5,8] and may be the S-protein receptor on these cells [32]. The phagocytes may thus produce their own adhesion molecules, which bind to cellular receptors and take part in the attachmetit and also enhance the Fc and C3b receptor activities [32] of the cells in the tissues. These functions, together with the capacity of S-protein to inhibit the lytic effect of the phagocyte complement components and its possible involvement in the regulation of macrophage-derived coagulation factors, demonstrate that synthesis of S-protein by mononuclear phagocytes may be of great biological importance in the local tissue environment.…”
Section: Discussionmentioning
confidence: 99%